2020
DOI: 10.1038/s41467-020-15136-9
|View full text |Cite
|
Sign up to set email alerts
|

A shift in glutamine nitrogen metabolism contributes to the malignant progression of cancer

Abstract: Glucose metabolism is remodeled in cancer, but the global pattern of cancer-specific metabolic changes remains unclear. Here we show, using the comprehensive measurement of metabolic enzymes by large-scale targeted proteomics, that the metabolism both carbon and nitrogen is altered during the malignant progression of cancer. The fate of glutamine nitrogen is shifted from the anaplerotic pathway into the TCA cycle to nucleotide biosynthesis, with this shift being controlled by glutaminase (GLS1) and phosphoribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
174
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 178 publications
(176 citation statements)
references
References 64 publications
1
174
0
1
Order By: Relevance
“…[33] Cancer cells thus use glutamine to synthesize aspartate. [18,33] Glutamic-oxaloacetic transaminase 1 (GOT1), a cytosolic enzyme, synthesizes intracellular aspartate by transferring the nitrogen of glutamate to oxaloacetate (Figure 2A). [30,31,34] The F I G U R E 3 Tumor carbon metabolism is dependent on glucose oxidation rather than on glutaminolysis in vivo.…”
Section: Glutamine As a Nitrogen Donor For De Novo Nucleotide Biosyntmentioning
confidence: 99%
See 4 more Smart Citations
“…[33] Cancer cells thus use glutamine to synthesize aspartate. [18,33] Glutamic-oxaloacetic transaminase 1 (GOT1), a cytosolic enzyme, synthesizes intracellular aspartate by transferring the nitrogen of glutamate to oxaloacetate (Figure 2A). [30,31,34] The F I G U R E 3 Tumor carbon metabolism is dependent on glucose oxidation rather than on glutaminolysis in vivo.…”
Section: Glutamine As a Nitrogen Donor For De Novo Nucleotide Biosyntmentioning
confidence: 99%
“…[45] Metabolic flux analysis of glucose and glutamine in cancer cells, performed by direct measurement in vivo, recently revealed that glycolysis serves as a major carbon-replenishing pathway for the TCA cycle in a variety of cancer types, including non-small cell lung cancer and glioblastoma ( Figure 3A). [18,[45][46][47][48][49][50][51] Lactate produced from glucose is released into the extracellular space, from where it is taken up by cancer cells and used for replenishment of the TCA cycle. [49,50] Whereas lung cancer cells in monolayer culture in vitro tend to use glutamine as a substrate for the TCA cycle, they use glucose instead of glutamine in the tumor microenvironment in vivo, a situation in which glutamine uptake by cancer cells is extremely limited.…”
Section: Glucose-derived Carbon Can Compensate For the Anaplerotic Rementioning
confidence: 99%
See 3 more Smart Citations